Experimental Study on Seismic Performance of Strap-Braced Cold-Formed Steel Shear Walls. Issue 2 (February 2013) - Zeynalian, Mehran; Ronagh, Hamid
This paper presents a detailed investigation of the lateral performance of X-strap braced cold-formed steel shear walls and their response modification factor, R . Four full-scale 2.4 × 2.4 m specimens with different configurations were tested, and their responses recorded under a standard cyclic loading regime. Of particular interest were the specimens' maximum lateral load capacity and deformation behaviour as well as a rational estimation of the seismic response modification factor. The study also looks at the failure modes of the system and investigates the main factors contributing to the ductile response of the cold formed steel (CFS) shear walls in order to suggest improvements so that the shear steel walls respond plastically with a significant drift and without any risk of brittle failure, such as connection failure or stud buckling. The walls tested have different number of strap elements with different angles, and brackets. The study shows that the performance of this kind of CFS lateral resistant system under cyclic loads is satisfactory; and can be considered reliable. A discussion on the calculated response factors in comparison to those suggested in the relevant codes of practice is also presented.